Effect of Different Escape Vent on Collapsible Pot For Catching Mud Crab - Iskandar, Dahri (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
The objective of this research was to obtain optimum shape of escape vent to mud crab catch.  The research used common fishermen’s pot for catching mud crabs. Three types of escape vent were installed in the pot i.e. rectangular shaped escape vent, Ship Same Side Corner Rectangle (S3CR), circle shaped  escape vent while non escape vent pot was used as control. Result of research indicated that total catch of each escape vent type was as follow: circle shaped escape vent pot was 57 fishes or equal with 21.84% of total catch, S3CR shaped escape vent pot was 46 fishes or equal with 17.62 % of total catch and rectangular shaped escape vent pot was36 fishes or similar with 13.79 % of total catch. Kruskall-Wallis test also indicated that there was significantdifferent of total catch between different type of escape vent pot (P=0.000; Chi-Square = 22.659). Mud  crab catch of S3CR shaped escape vent pot was showing the highest catch than other type of escape vent pot. Kruskall- Wallis test on total catch of mud crab also indicated significantly different among different type of escape vent (P=0.005; Chi-Square = 12.667). Keywords: Collapsible pot, escape vent, mud crab, catch